Preliminary Study on the Agar Quality of Laboratory-Generated Carposporelings of Gracilariopsis bailinae Zhang et Xia Grown in the Field (A short communication) - Rabanal, Susan (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The agar quality (gel strength, gelling and melting temperature) of laboratory-generated carposporelings of Gracilariopsis bailinae grown in the field for six weeks off Amunitan, Gonzaga, Cagayan was investigated. Cut sporelings grown at 1.0 m depth showed good quality agar (492 gm cm-2 gel strength, 43oC gelling temperature, 84oC melting temperature). This constitutes the first report on the agar quality of this species from this area.
Keywords: Gracilariopsis; agar; agarophyte